2017
DOI: 10.1080/1828051x.2017.1364985
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value and fatty acid content of soybean plant [Glycine max (L.) Merr.] during its growth cycle

Abstract: Soybean [Glycine max (L.) Merr.] is mostly cultivated for grain in Asia, South and North America and it may be grown to be used as high-protein forage for grazing, haying or ensiling. Field trials with the soybean cultivar Eiko were conducted in NorthWest Italy to determine its chemical composition, gross energy, in vitro true digestibility (IVTD), neutral detergent fibre digestibility (NDFD) and fatty acid (FA) profile during growth. Herbage samples of cultivar Eiko were collected at seven progressive morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…is one of the most important plant proteins sources consumed by humans and animals. It is attracting growing interest as a source of high-protein forage in Europe [1], North America [2], South Asia [3], and Japan [4]. The few studies that have examined the antioxidant activities and phenolic profiles of soybean seed found that soybean varieties differ in their antioxidant properties, total phenolic contents, anthocyanin and flavonoid levels [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is one of the most important plant proteins sources consumed by humans and animals. It is attracting growing interest as a source of high-protein forage in Europe [1], North America [2], South Asia [3], and Japan [4]. The few studies that have examined the antioxidant activities and phenolic profiles of soybean seed found that soybean varieties differ in their antioxidant properties, total phenolic contents, anthocyanin and flavonoid levels [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Because the polyphenolic contents and antioxidant capacities of crops, including perilla [29], quinoa [30] and safflower [31] may also vary in the whole plant during growth, it is important to identify the growth stage at which the plant has the maximum antioxidant properties for the production of bioactive compounds from crops or agricultural by-products or for forage as a possible source of antioxidants in livestock. The feeding value of soybean forage and the effects of plant ageing on chemical composition, gross energy, in vitro true digestibility, neutral detergent fiber digestibility, and fatty acid profile have been documented in the literature [1]. The innovative aspect of the present study was to characterize the antioxidant activities and phenolic composition of the soybean plant during its growth cycle, because, to the best of our knowledge, no research has been reported in literature about the change of these parameters during plant ageing.…”
Section: Introductionmentioning
confidence: 99%
“…effects on insulin secretion and energy metabolism, reduces the risk of breast cancer, and is compatible with many specialized diets (31)(32)(33).…”
Section: Soyabean (Glycine Max)mentioning
confidence: 99%
“…Os primeiros registros do uso da planta inteira de soja (PS) na nutrição de ruminantes data no início dos anos 90 na forma de pastejo quando intempéries climáticos afetavam a qualidade e/ou produtividade de grãos e a lavoura era destinada ao consumo animal , pois à época, ainda não se considerava a produção de sillagem de planta inteira de soja (SS) uma forma alternativa de uso da PS para grão. (SHAEFFER et al, 2001;SEITER et al, 2004;PEIRETTI et al, 2017), demonstrando que os resultados são inerentes a inúmeros fatores e que devem ser avaliados caso a caso.…”
Section: Introductionunclassified
“…Houve efeito de interação entre EF e tempo (P < 0,001) em que a temperatura da SS em R3 foi superior aos demais EF a partir de 24 h não diferindo de R4 a partir de 108 h.2.6 DISCUSSÃOA composição morfológica da PS seguiu o mesmo comportamento ao longo do ciclo reprodutivo independente da unidade na qual foi expressa. Porém o peso médio da PS não acompanha o comportamento de um componente individualmente, mas sim a combinação da proporção entre eles, tornando a magnitude do efeito de EF sobre ela, dependente de fatores ligados a características agronômicas, de cultivo e climáticos(SHAEFFER et al, 2001;SEITER et al, 2004;PEIRETTI et al, 2017) Gebrehanna et al (2014). em revisão, demonstraram haver relação inversa entre a produção de efluente com o teor de MS do material ensilado.…”
unclassified